The Effectiveness of Solution-Focused Brief Therapy (SFBT)-Based Group Counseling in Reducing Delinquency in High School Students - Shine Ayariha Hafshah (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2025)
This study aimed to examine the effectiveness of Solution-Focused Brief Therapy (SFBT)-based group counseling in reducing delinquency among high school students. The research employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The study was conducted at SMA Nurul Huda involving 10 students selected through purposive sampling based on their moderate to high levels of delinquent behavior. Data were collected through delinquency questionnaires, observations, and documentation. The counseling intervention consisted of six SFBT-based group counseling sessions focusing on students’ strengths, future goals, and solution-building processes. The findings revealed that students demonstrated significant reductions in delinquent behavior after participating in the counseling program. Improvements were observed in emotional regulation, peer interaction, classroom participation, and compliance with school rules. Statistical analysis using the Paired Sample t-Test showed a significant difference between pretest and posttest scores, indicating that SFBT-based group counseling was effective in reducing student delinquency. The study concludes that solution-focused group counseling provides a practical, supportive intervention model for helping adolescents achieve positive behavioral change in school counseling settings.